The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1620/tjem.225.123
|View full text |Cite
|
Sign up to set email alerts
|

Eating Buckwheat Cookies Is Associated with the Reduction in Serum Levels of Myeloperoxidase and Cholesterol: A Double Blind Crossover Study in Day-Care Centre Staffs

Abstract: Buckwheat food is a good source of antioxidants, e.g. rutin, and other beneficial substances. Here we investigated the effects of the intake of common buckwheat (low rutin content) and tartary buckwheat cookies (high rutin content) on selected clinical markers. A double blind crossover study was performed among female day-care centre staffs (N = 62) from five day-care centres. Participants were randomly divided into two groups. The first group initially consumed four common buckwheat cookies per day (16.5 mg r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 29 publications
0
47
2
3
Order By: Relevance
“…Serum total cholesterol levels in day-care staff were found to be reduced by eating cookies prepared with common or tartary buckwheat; however, no differences were observed between the two buckwheat groups (Wieslander et al, 2011). Buckwheat is rich in rutin, and its content in tartary buckwheat is estimated to be approximately 100 times that in common buckwheat (Yasuda et al, 1992).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Serum total cholesterol levels in day-care staff were found to be reduced by eating cookies prepared with common or tartary buckwheat; however, no differences were observed between the two buckwheat groups (Wieslander et al, 2011). Buckwheat is rich in rutin, and its content in tartary buckwheat is estimated to be approximately 100 times that in common buckwheat (Yasuda et al, 1992).…”
Section: Discussionmentioning
confidence: 95%
“…Flavonoids are reported to have beneficial biological activities, such as the prevention of atherosclerosis and obesity, through their antioxidative or anti-inflammatory effects (Grassi et al, 2010;Choi et al, 2006;Rivera et al, 2008). Wieslander et al (2011) demonstrated that the intake of common (16.5) or tartary (359.7 mg rutin-equivalent/day) buckwheat cookies resulted in a reduction of subjects' serum total cholesterol level. Moreover, He et al (1995) indicated that buckwheat intake was associated with lower serum total and LDL cholesterol levels in their epidemiologic study.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al [73] demonstrated that a high-fibre, low fat diet decreased the circulating MPO activity and the atherosclerosis risk in healthy adolescents. Additionally, the regular consumption of buckwheat cookies rich in rutin brought about lower activity of the circulating MPO in middle-aged females [91]. Similarly, a hypocaloric diet rich in cocoa extract markedly decreased the circulating MPO activity, but also the oxidised LDL-C level in humans [33].…”
Section: Effect Of Diet On Paraoxonase 1 and Myeloperoxidase Activitiesmentioning
confidence: 99%
“…All participants answered a general questionnaire with standardized questions on occupation, asthma, chronic diseases, demographic data and the home environment (Wieslander et al, 2011;Norbäck et al, 2015). Each subject was allergy tested in the beginning of the study by skin prick tests (ALK Abello SA, Madrid, Spain) for birch, timothy, mug worth, cat, dog, horse, house dust mites (D. pteronyssinus and D. farinae) and two types of mould (Cladosporium and Alternaria).…”
Section: Medical Investigationmentioning
confidence: 99%
“…The study was a part of a dietary crossover intervention study. For this indoor environment study, clinical data from all three investigations were used since for each participant the three tests were balanced with respect to the dietary intervention (Wieslander et al, 2011).…”
Section: Medical Investigationmentioning
confidence: 99%